Laser powder bed fusion of glass: A comparative study between CO2 lasers and ultrashort laser pulses - Seyfarth, Brian; Schade, Lisa; Matthaeus, Gabor; Ullsperger, Tobias; Heidler, Nils; Hilpert, Enrico; Nolte, Stefan (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
During the last decade, laser assisted additive manufacturing evolved to a serious alternative to traditional manufacturing methods. The greatest benefit lies in the realization of almost any desired geometry impossible to create with common molding or cutting processes. Due to the lack of linear absorption in the visible and near infrared, transparent dielectrics like glass are challenging materials for laser powder bed fusion (LPBF). Here, a comparative study on the additive manufacturing of pure fused silica glass parts is presented. For the fusion process, either a common CO2 laser system working at 10.6 μm or an ultrashort pulse (USP) fiber laser system at 1030 nm were applied. While the mid-infrared laser radiation from CO2-lasers is absorbed linearly, ultrashort laser pulses benefit from their extremely high peak power leading to strong nonlinear absorption. In contrast to alternative approaches [1], there was no need for binding materials. For both systems, a comprehensive parameter study is presented, highlighting major differences like surface quality, resolution and processing time.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Additive manufacturing; Glass; Laser processing; Selective laser melting; Ultrashort laser pulses